2020
DOI: 10.1111/and.13845
|View full text |Cite
|
Sign up to set email alerts
|

Application of ultrasound‐guided seminal vesicle radiography combining CT three‐dimensional reconstruction technique in transurethral seminal vesiculoscopy

Abstract: For the treatment of ejaculatory duct obstruction, transurethral seminal vesiculoscopy (TSV) is the most common method, but the success rate is much lower than studies that have reported. So we developed a new ultrasound‐guided seminal vesicle radiography (UGSVR) combining CT three‐dimensional reconstruction (CT‐TR) technique to improve the success rate of TSV. Between June 2018 and November 2019, 32 patients were enrolled and randomly assigned to two groups: experimental group (UGSvR combining CT‐TR) and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…us, the purpose of reducing intraoperative bleeding and shortening the operation time can be realized [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…us, the purpose of reducing intraoperative bleeding and shortening the operation time can be realized [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Transurethral seminal vesicle microscopy is emerging as an alternative method for the diagnosis and treatment of seminal vesicle and seminal tract disorders. Several studies have shown that transurethral vesicle microscopy can achieve good results in the treatment of recurrent hemospermia and concluded that transurethral vesicle microscopy is an effective and safe method for the treatment of spermatic diseases (27). In 2002, Yang et al used seminal vesicle endoscopy for the first time in the examination and treatment of seminal vesicle diseases, and they reported the safety of this method (28).…”
mentioning
confidence: 99%